Global inequalities at work work's impact on the health of individuals, families, and societies - Heymann, Jody, 1959- (New York ; Oxford : Oxford University Press, 2003)
Drawing on studies around the world, this book critically examines the many ways in which work is affecting health. It includes discussion of the ways in which working conditions affect income inequalities and health and the ways in which working conditions influence gender inequalities and health.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Industrial hygiene